Email von Georgina Beier - Beier, Georgina (Of Art Worlds - Collecting and Archiving Modern and Contemporary Art on the African Continent, 2016)
Copyright held by Iwalewahaus, CBCIU.
Keywords: Africa; Artists; Email; Nigeria; Art Collector; Art Collecting